2008
DOI: 10.4085/1062-6050-43.5.489
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Concepts for Elite Distance Runners Based on Macronutrient and Energy Expenditure

Abstract: Nutrition concepts must be differentiated for EDR according to metabolic and anthropometric characteristics of the runners and their special training emphases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…The age and sex-specific Estimated Average Requirement (EAR) of essential minerals and vitamins [24] was used as reference for expressing the individual daily intake of a nutrient into the respective probability of nutrient adequacy (PA) [25]. The requirement for iron was based on 12 % bioavailability and that for zinc on medium bioavailability [24].…”
Section: Estimated Probability Of Nutrient Adequacies For Vitamins Anmentioning
confidence: 99%
“…The age and sex-specific Estimated Average Requirement (EAR) of essential minerals and vitamins [24] was used as reference for expressing the individual daily intake of a nutrient into the respective probability of nutrient adequacy (PA) [25]. The requirement for iron was based on 12 % bioavailability and that for zinc on medium bioavailability [24].…”
Section: Estimated Probability Of Nutrient Adequacies For Vitamins Anmentioning
confidence: 99%
“…Despite these factors, authors have demonstrated that there may be under or overestimation of results found by them (19,20) . Based on this reality, even if the calculations of the energetic need estimation (ENI) in the present study point to be inadequate, the street runners still present caloric cost below the expected values for running or marathon runners practitioners, estimated between 3.000kcal and 5,000kcal (6,21) . When caloric intake was considered according to body weight, the group of runners presented mean intake of 28kcal/kg of weight/day, much below the DSBME (22) guidelines, between 30 and 50kcal/kg of body weight/day according to the kind of exercise practiced.…”
Section: Discussionmentioning
confidence: 58%
“…Many factors should be considered for a suitable nutritional planning, among these, energetic adjustment of the diet, distribution of macronutrients and suitable supply of vitamins and minerals (3) . Studies (4)(5)(6) have presented data concerning the anthropometric and/or nutritional profile of elite athletes whose practiced modalities involve running (e.g. marathon, track and field, endurance sports, etc); however, little is known about these characteristics in street running practitioners or the so-called 'recreational' athletes.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it was not mentioned that the energetic ingestion was simply below the recommendations, rather, that when it was compared to the values suggested by the DRIs (1) , Guideline of the Brazilian Society of Sports Medicine (2) and other authors (3,4) , the energetic ingestion was kept below the optimum levels, which could reflect on the general performance as a whole. Therefore, it is interesting to stress that the presented results should be better investigated, especially concerning the evaluation of macronutrients involving recreational street runners.…”
Section: Reply Lettermentioning
confidence: 99%